2019
DOI: 10.1259/bjr.20190742
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nanoparticle uptake, intracellular distribution, and retention with docetaxel to enhance radiotherapy

Abstract: Objective: One of the major issues in current radiotherapy (RT) is the normal tissue toxicity. A smart combination of agents within the tumor would allow lowering the RT dose required while minimizing the damage to healthy tissue surrounding the tumor. We chose gold nanoparticles (GNPs) and docetaxel (DTX) as our choice of two radiosensitizing agents. They have a different mechanism of action which could lead to a synergistic effect. Our first goal was to assess the variation in GNP uptake, distribution, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 74 publications
(73 reference statements)
1
37
0
Order By: Relevance
“…Furthermore, the GNPs appear to localize closer to the nuclei in the CAFs and HeLa while being more distributed throughout the cells in the FBs. It is known that the vesicles and organelles in the cells are transported along the microtubules (MTs) within the cells 43 . Similarly, vesicles containing GNPs within the cell have previously been shown to travel along the MTs following uptake 44 .…”
Section: Results Characterization Of Gold Nanoparticle Complex ( Gnp mentioning
confidence: 99%
“…Furthermore, the GNPs appear to localize closer to the nuclei in the CAFs and HeLa while being more distributed throughout the cells in the FBs. It is known that the vesicles and organelles in the cells are transported along the microtubules (MTs) within the cells 43 . Similarly, vesicles containing GNPs within the cell have previously been shown to travel along the MTs following uptake 44 .…”
Section: Results Characterization Of Gold Nanoparticle Complex ( Gnp mentioning
confidence: 99%
“…The reduced accumulation of NPs in cells treated with 10 nM DTX, as compared to 0 nM DTX, could be due to the fragmented division seen in cells treated with 10 nM DTX ( Figure 2 f) [ 40 ]. The greater accumulation of NPs in cells treated with 50 nM DTX could be due to the cell cycle arrest in G2/M phase [ 20 , 40 , 41 ]. We also examined the NP accumulation when cells were treated with 1 nM DTX and observed an outcome much closer to the control and 10 nM conditions, as expected (see Supplementary Materials S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that the uptake of NPs, including GNPs, is increased when the cell population is synchronized in the G 2 /M phase [85,159]. This suggests the use of DTX concomitantly with other drugs or radiation, which was tested by Bannister et al as seen in Figure 8 [160]. DTX used as a synchronizing agent when paired with GNPs lead to higher uptake, a higher localization of the GNPs to the nucleus, and a larger, synergistic response to radiotherapy.…”
Section: Rationale For Gold Nanoparticles In Chemoradiotherapymentioning
confidence: 95%
“…DTX used as a synchronizing agent when paired with GNPs lead to higher uptake, a higher localization of the GNPs to the nucleus, and a larger, synergistic response to radiotherapy. Reproduced with permission from [160]. Copyright 2020 British Journal of Radiology.…”
Section: Rationale For Gold Nanoparticles In Chemoradiotherapymentioning
confidence: 99%